DEVELOPMENT OF INDONESIAN SHARIA BANKS WITH MALAYSIA COMPARATION METHOD (STUDY OF HISTORY, PRODUCTS AND LEGAL ASSETS) - Mukti, Hagi Hutomo (Lambung Mangkurat Law Journal, 2020)
Sharia banking is developed in response to economic and cultural groups that are used to accommodate those who want the services to be carried out with Islamic sharia principles and morals. The development of Sharia banks in Indonesia and Malaysia needs to be studied more deeply because Malaysia first established Sharia banks in 1983 through Bank Islam Malaysia Berhad (BIMB) while the first sharia bank in Indonesia, which named Bank Muamalat, was burned in 1991, which determines the direction of the progress of sharia banks in Indonesia with the provisions of Law Number 10 of 1998 concerning Banking. Determine the amount of assets from banks that have a ratio of 1: 10 with Malaysia considering the assets of sharia banks in Indonesia amounted to US $ 35.62 billion while Malaysia reached US $ 423.2 billion. This study focuses on the factors and effects of legal products from the two countries in order to get more comprehensive study and know the relation between the legal products with sharia banking development in Indonesia and Malaysia.